Medium chain triglycerides dose-dependently prevent liver pathology in a rat model of non-alcoholic fatty liver disease. (February 2013) - Ronis, Martin J J; Baumgardner, January N; Sharma, Neha; Vantrease, Jamie; Ferguson, Matthew; Tong, Yudong; Wu, Xianli; Cleves, Mario A; Badger, Thomas M
Metabolic syndrome is often accompanied by development of hepatic steatosis and less frequently by non-alcoholic fatty liver disease (NAFLD) leading to non-alcoholic steatohepatitis (NASH). Replacement of corn oil with medium chain triacylglycerols (MCT) in the diets of alcohol-fed rats has been shown to protect against steatosis and alcoholic liver injury. The current study was designed to determine if a similar beneficial effect of MCT occurs in a rat model of NAFLD. Groups of male rats were isocalorically overfed diets containing 10%, 35% or 70% total energy as corn oil or a 70% fat diet in which corn oil was replaced with increasing concentrations of saturated fat (18:82, beef tallow: MCT oil) from 20% to 65% for 21 days using total enteral nutrition (TEN). As dietary content of corn oil increased, hepatic steatosis and serum alanine amino transferases were elevated ( P < 0.05). This was accompanied by greater expression of cytochrome P450 enzyme CYP2E1 ( P < 0.05) and higher concentrations of polyunsaturated 18:2 and 20:4 fatty acids (FA) in the hepatic lipid fractions ( P < 0.05). Keeping the total dietary fat at 70%, but increasing the proportion of MCT-enriched saturated fat resulted in a dose-dependent reduction in steatosis and necrosis without affecting CYP2E1 induction. There was no incorporation of C8-C10 FAs into liver lipids, but increasing the ratio of MCT to corn oil: reduced liver lipid 18:2 and 20:4 concentrations; reduced membrane susceptibility to radical attack; stimulated FA β- and ω-oxidation as a result of activation of peroxisomal proliferator activated receptor (PPAR)a, and appeared to increase mitochondrial respiration through complex III. These data suggest that replacing unsaturated fats like corn oil with MCT oil in the diet could be utilized as a potential treatment for NAFLD.